Mohammad Natsir Thought on Reactualising Religious Nationalism in Indonesia - Ferdi Yufriadi (Hakamain: Journal of Sharia and Law Studies, 2023)
Mohammad Natsir's nationalism is a significant phenomenon in the history of Indonesia that influenced the process of nation-building during the early days of independence. This journal aims to investigate the crucial role of the nationalist figure Haji Mohammad Natsir in fostering the spirit of nationalism and how his thoughts shaped the national identity of Indonesia. The research methodology employed in this journal is a qualitative approach through narrative analysis and relevant primary sources related to Natsir's role in Indonesia's struggle for independence. The sources used include speeches, writings, and Natsir's biography, as well as works by historians and researchers who have examined his significant role in the nation's history. The research findings indicate that Natsir was a visionary and influential nationalist figure in shaping Indonesia's national identity. His nationalist views emphasized unity, integrity, and national identity based on the values of Pancasila and Islam. This ideology played a key role in fostering a sense of unity and nationalism among the Indonesian populace during challenging times after independence. Additionally, the journal highlights Natsir's role in advancing national education and culture. He advocated for the development of the Indonesian language as a unifying language and promoted Indonesian arts, literature, and culture to strengthen the national identity. Natsir's nationalism played a significant role in the process of shaping Indonesia's national identity. His thoughts on unity, justice, and the noble values of Indonesia have helped guide the nation towards a strong national identity. Therefore, a deeper understanding of Natsir's role in national history provides valuable insights into how nationalist figures can shape the national identity of a nation.